Intestinal Protozoa Infections in Relation to Nutritional Status of the Students Mandangin Island Elementary School 6 in Sampang Regency - Marlinda Kurniati; Budiono Budiono; Sri Wijayanti Sulistyawati (Faculty of Medicine Universitas Airlangga, 2019)
Introduction: Intestinal protozoa infections is a tropical infectious disease that can be found mainly in developing countries. It will cause some health problem such as undernutrition. This study was aiming to determine the correlation between the incidence of intestinal protozoa infections with the nutritional status of students Mandangin Island Elementary School 6 in Sampang Regency.Methods: This research used the cross-sectional study as the design and performed by doing a lab examination to determine the incidence of protozoa infections and analyze whether it has any correlation with changes in host nutritional status, recruited from students Mandangin Island Elementary School 6, from 19th to 21st of July 2017. Results: On microscopic examination found that 71.4% (n=30) samples are positive and 28,6% (n=12) are negative. On BMI-for-age measurement there are 4,8% obesity, 7,1% overweight, 73,8% normal, 9,5% thinness, and 4,8% severe thinness. Meanwhile, on height-for-age measurement there are 73,8% normal and 26,2% stunted . The incidence of intestinal protozoa infections was correlated with the nutritional status using SPSS (p= 0,375, p= 0,539, a= 5%).Conclusion: There was no significant correlation between intestinal protozoa infections with the nutritional status of students Mandangin Island Elementary School 6 in Sampang Regency. These conditions caused by the pathogenicity stage to cause a decrease in the nutritional state has not been reached.